Hemochromatosis gene (HFE) mutations in South East Asia: a potential for iron overload. - Pointon, J; Viprakasit, V; Miles, K; Livesey, K; Steiner, M; O'Riordan, S; Hien, T; Merryweather-Clarke, A; Robson, K (2003)
Hereditary hemochromatosis (HH) is an autosomal recessive disease caused by mutations in the HFE gene that mainly affects populations of European descent. Recently a novel mutation (IVS5+1 G-->A) has been described in a Vietnamese patient with HH that was not detected in a European control population. We have developed a novel method to screen for this mutation based on restriction enzyme digestion of a PCR product using a modified forward primer. We have screened 314 Vietnamese people from several ethnic groups and 154 people from Thailand for this mutation and have detected two heterozygotes in the Vietnamese subjects (allele frequency 0.003). Analysis of these heterozygotes indicates that the mutation is on the same haplotype as that found in the original proband. Screening for the widely distributed HFE mutation, H63D, gave an allele frequency of 0.049 in the Vietnamese subjects and 0.032 in the subjects from Thailand. This is the first report of H63D allele frequencies in these populations. We suggest that the presence of the IVS5+1 G-->A and H63D mutations should be considered when investigating iron overload in Vietnamese patients and those of mixed origin as co-inheritance of both mutations is likely to be a risk factor for iron overload.